Observations of the Effects of Maternal Fasting Plasma Glucose Changes in Early Pregnancy on Fetal Growth Profiles and Birth Outcomes - Guo, Fei; Liu, Yindi; Ding, Zheng; Zhang, Yong; Zhang, Chen; Fan, Jianxia (Frontiers in Endocrinology, 2021)
Introduction: Although the role of maternal hyperglycaemia on birth outcomes is clear, literature regarding foetal growth is scarce. We examined the possible associations between maternal fasting plasma glucose (FPG) and foetal growth. Materials and methods: A total of 35981 singleton-pregnant women with FPG in the first trimester were included. Foetal growth parameters were measured during pregnancy by ultrasound at mid and late pregnancy. Information on birth characteristics was retrieved from medical records. We used multivariable linear and logistic regression to determine the associations between FPG and z-scores of foetal parameters and risks of birth outcomes and to assess effect modification by maternal characteristics. Results: A per-unit increase in FPG levels was negatively associated with foetal parameters in mid-pregnancy, but positively correlated with those in late pregnancy and with birth characteristics. The effect estimates in late pregnancy were attenuated by maternal pre-pregnancy body mass index (BMI). A significant relationship between FPG and abdominal circumference (AC), an indicator of foetal adiposity, was sustained in subgroups of women with advanced age, positive family history of diabetes and multiparity in fully adjusted models. After stratification by BMI, high FPG was associated with accelerated AC only in normal controls (0.044 SD, 95% CI: 0.010, 0.079) and overweight/obese women (0.069 SD, 95% CI: -0.002, 0.140) but not in underweight women. High FPG was an independently risk factor for large-for-gestational age in the whole group and stratified-subgroups. Conclusions: Increased FPG in early pregnancy is closely related to foetal growth. Maternal characteristics may modify the associations between FPG and foetal adiposity in late pregnancy.